The Impact of 120 Minutes of Match-Play on Recovery and Subsequent Match Performance: A Case Report in Professional Soccer Players - Nathan Winder; Mark Russell; Robert J. Naughton; Liam D. Harper (MDPI AG, 2018)
The influence of a match including extra-time (ET) on subsequent 90 min match performance and recovery has not been investigated. Four professional soccer players played in three competitive matches in a 7-day period: matches one (MD1) and three (MD3) lasted 90 min and match 2 (MD2) lasted 120 min (i.e., included ET). Physical (total and high-intensity (HI) distance covered, accelerations and decelerations, and mechanical load) and technical performances (pass and dribble accuracy) were analyzed throughout match-play. Subjective measures of recovery and countermovement jump (CMJ) height were made 36-42 h post-match. Post-MD2, there were very or most likely harmful effects of ET on CMJ height (−6 ± 9%), muscle soreness (+18 ± 12%), and fatigue (+27 ± 4%) scores, and overall wellness score (−13 ± 5%) compared to post-MD1. Furthermore, there were very likely harmful effects on muscle soreness (+13 ± 14%), wellness scores (−8 ± 10%), and CMJ height (−6 ± 9%) post-MD3 vs. post-MD1. There was a possibly harmful effect of ET on HI distance covered during MD3, along with reductions in pass (−9.3%) and dribble (−12.4%) accuracy. An ET match negatively impacted recovery 36 h post-match. Furthermore, in some players, indices of performance in a 90 min match played 64 h following ET were compromised, with subsequent recovery also adversely affected.